What went wrong? : case histories of process plant disasters - Kletz, Trevor A. (Elsevier, 1999)
Expert Trevor Kletz examines the causes and aftermaths of numerous plant disasters--almost every one of which could have been prevented. Case histories illustrate what went wrong, why it went wrong, and then guide you in how to circumvent similar tragedies. Learn from the mistakes of others. This invaluable and respected book examines the causes and aftermaths of numerous plant disasters - almost every one of which could have been prevented. Case histories illustrate what went wrong and why it went wrong, and then guide you in how to circumvent similar tragedies.* Learn from the.